COMMUNICATION MODEL OF CORRECTIONAL OFFICERS TO RECIDIVIST INMATES IN ENCOURAGING PARTICIPATION IN SELF-RELIANCE DEVELOPMENT PROGRAMS AT CLASS I CORRECTIONAL FACILITY MEDAN - Dzurgi Gultom, Mikael Theotista; Soge, Markus Marselinus (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study examines the communication patterns used by correctional officers in engaging recidivist inmates at the Class I Correctional Facility Medan, in response to the high rate of recidivism in Indonesia and the challenges of overcrowding. The research aims to describe how communication is applied in the rehabilitation process and to identify the obstacles faced in encouraging inmate participation in independence development programs. Using a descriptive qualitative approach, data were collected through in-depth interviews, observations, and documentation involving correctional officers and recidivist inmates selected purposively. The findings show that interpersonal communication characterized by empathy, openness, and a persuasive approach plays an important role in increasing inmate participation in rehabilitation activities, particularly vocational skills training programs. However, the implementation of effective communication is still constrained by several factors, including overcrowded conditions, a limited number of officers, lack of communication training, and peer pressure among inmates. These challenges hinder the optimization of rehabilitation programs. Therefore, strengthening communication capacity, increasing the number of officers, and improving institutional support are necessary to enhance the effectiveness of inmate rehabilitation and reduce recidivism rates. Keywords: Communication Model; Recidivist Inmates; Independence Development; Correctional Facility; Rehabilitation